2015
DOI: 10.3109/1354750x.2015.1068863
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in cortisol biomarkers in Hispanic mothers living in an agricultural region

Abstract: Context Characterization of stress exposure requires an understanding seasonal variability in stress biomarkers. Objective To compare acute and chronic stress biomarkers between two seasons in a cohort of rural, Hispanic mothers. Methods Stress questionnaires and cortisol measurements (hair, blood, saliva) were collected in the summer and fall. Results Cortisol biomarkers were significantly different and stress questionnaires were significantly correlated between seasons. Discussion The variability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Study participants were recruited from the larger CHC cohort to participate in this nested study of environmental influences on urinary miRNA. The CHC cohort has been described in two recent studies, Thompson et al, 2014 and Smith et al, 2015. Briefly, in 2011, 27 women of childbearing age (18–49 years) and one child from each household were recruited from the larger CHC cohort to participate in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study participants were recruited from the larger CHC cohort to participate in this nested study of environmental influences on urinary miRNA. The CHC cohort has been described in two recent studies, Thompson et al, 2014 and Smith et al, 2015. Briefly, in 2011, 27 women of childbearing age (18–49 years) and one child from each household were recruited from the larger CHC cohort to participate in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly all speak Spanish as a primary language. A detailed description of the nested study participants can be found in Smith et al 2015.…”
Section: Methodsmentioning
confidence: 99%
“…In future studies, more medical/health sciences and male participants should be included. Although circadian variations in cortisol were taken into consideration, seasonal variations in cortisol were not considered as recent studies indicated that cortisol does not have seasonal differences (Smith et al, 2015).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In the present study, we found no statistically significant differences in HCC between the spring (T1) and fall (T2) measurements. Seasonal effects and effects of duration of sample storage on measured HCC have been reported in previous research [ 61 , 62 , 63 ]. According to these studies, one would expect lower HCC for the summer season (which we measured at T2) and lower values for the samples that had been stored for longer (which concerns all samples taken at T1, because they were analysed only after T2).…”
Section: Discussionmentioning
confidence: 57%